A Mirage of a dislocated lens in uveitis - Nadeem, Sana; Naeem, BA (Pakistan Journal of Ophthalmology, 2020)
We present a very strange case of a 44-year-old diabetic lady who presented with what appeared to be a cataractous lens dislocated in the anterior chamber of her left eye, following weight bearing, a week prior to presentation. The possibility of this being the lens became doubtful on slit lamp examination, as keratic precipitates and flare was noted bilaterally. Her pupil was miosed rendering posterior segment view extremely difficult. Subconjunctival mydriacaine and dexamethasone were given along with topical steroids and cycloplegics, which allowed a better view of the pupillary area, revealing a hint of a nuclear sclerotic cataract, very well in its natural anatomical location. This is a rare presentation of exudate in anterior uveitis presenting as a lens-like mass, producing such an illusion, as to completely baffle doctors regarding its diagnosis. The mass-like exudate subsequently diminished with topical therapy, and disappeared in around a week’s time. Both eyes are quiet at a five months follow-up.